Guerra e Natura nel poema di Nonno di Panopoli (Gilgameš, 2016)
This paper focuses on the first part of Nonnus’ Dionysiaca, book XXII, that recounts the preliminary stages of Dionysus’ war against Indians. The scene opens with the description of an idyllic landscape. When the god reaches Hydaspes river, nature is involved by typical Dionysiac phenomena: water becomes wine and milk flows from the springs. Deriades’ army is about to make an assault, but it’s defeated by Dionysus’ plant-weapons. The paper aims to underline the contrast between calm scenery and brutality of war, a topic that will be popular in modsuggests that the encounter has a cosmic and ideological value. erne literatures. I explore the way Nonnus creates tension before the battle and then represents an unconventional fight, at least at first bloodless. The poet, making nature joining the struggle, suggests that the encounter has a cosmic and ideological value.